Description of Neoxantholinus koghianus sp. n. and its larva from New Caledonia (Coleoptera, Staphylinidae, Xantholinini) - Bordoni, Arnaldo; Staniec, Bernard (Zootaxa, 2018)
Neoxantholinus koghianus sp. n. (Coleoptera, Staphylinidae, Xantholinini) and the detailed external structure of its late (L2-3) and early (L1) larval instars from New Caledonia are described and illustrated. The morphological differences between L1 and L2-3 of N. koghianus sp. n. involve four characters. Diagnostic larval characters for the genus Neoxantholinus are given for the first time.